TOMI digital y Liveworksheets como recursos didácticos para el aprendizaje de Biología Celular con los estudiantes de segundo semestre de la carrera de Pedagogía de las Ciencias Experimentales Química y Biología - Ayala Caminos, Dayana Estefania (2023)
In recent years, there has been much discussion about the diversity of educational platforms and their benefits, which, undoubtedly, nowadays is definitely a good way of learning, however, students have been limited to the use of certain digital resources for their learning process, either during their participation with exhibitions, during classes or as academic reinforcement material. Therefore, this study had the objective of proposing the use of TOMi Digital and Live worksheets as didactic resources for learning Cell Biology. This research had a qualitative approach, non-experimental design and descriptive, field and bibliographic level. For the analysis of the information the following methods were applied: inductive, analytical and synthetic, and for the collection of data the survey technique was used, applied by means of a questionnaire to 37 students enrolled in the second semester of the Pedagogy of Experimental Sciences, Chemistry and Biology course. After interpreting the data and analyzing the results, it was possible to conclude that both TOMi Digital and Liveworksheets are catalogued as important platforms that provide support to educational contexts allowing the creation of interactive learning environments where greater attention, better performance and knowledge retention predominate. Therefore, the continuous use of these two interactive tools was suggested to strengthen the learning of the contents of this subject.